2011
DOI: 10.2172/1029824
|View full text |Cite
|
Sign up to set email alerts
|

Survey of techniques for reduction of wind turbine blade trailing edge noise.

Abstract: Aerodynamic noise from wind turbine rotors leads to constraints in both rotor design and turbine siting. The primary source of aerodynamic noise on wind turbine rotors is the interaction of turbulent boundary layers on the blades with the blade trailing edges. This report surveys concepts that have been proposed for trailing edge noise reduction, with emphasis on concepts that have been tested at either sub-scale or full-scale. These concepts include trailing edge serrations, low-noise airfoil designs, trailin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It is well known that many species of owls have the unique ability to fly almost silently, and this topic is now widely studied as it could provide novel designs which allow for noise reduction in bladed systems, such as helicopter rotors and wind turbines (Barone 2011). Certain features of the wings of owls are known to be particularly effective in reducing scattered noise (Graham 1934): the fringed or serrated trailing edge (Howe 1991); the downy coat on the upper surface of the wing (Clark 2014); and the flexible and porous qualities of the feathers at the trailing edge (Jaworski & Peake 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that many species of owls have the unique ability to fly almost silently, and this topic is now widely studied as it could provide novel designs which allow for noise reduction in bladed systems, such as helicopter rotors and wind turbines (Barone 2011). Certain features of the wings of owls are known to be particularly effective in reducing scattered noise (Graham 1934): the fringed or serrated trailing edge (Howe 1991); the downy coat on the upper surface of the wing (Clark 2014); and the flexible and porous qualities of the feathers at the trailing edge (Jaworski & Peake 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The best design for the trailing edge will be a compromise between manufacturing cost, aerodynamic performance, and noise. Trailing-edge noise is mainly caused by the interaction of the boundary layer with the trailing edge, by airflow separation, and by vortex shedding (for blunt trailing edges, referred to as bluntness noise) 22 . The sharp edges and irregular transitions of options V1, V2 and V3, will contribute significantly to such turbulent interactions and thus to noise.…”
Section: B Design Parameters Of the Rotormentioning
confidence: 99%
“…Finally, in response to noise concerns, wind-technology developers are investigating numerous ways to suppress noise including passive noise reduction blade designs, active aerodynamic load control, new research on inflow turbulent and turbine wakes, low-noise brake linings, and cooling fan noise mufflers (Leloudas et al, 2009;Wilson et al, 2009;Barone, 2011;Petitjean et al, 2011), some of which have been shown to lower annoyance when applied (Hoen et al, 2010;Hessler, 2011). How these strategies might eventually affect setback and noise regulations and guidelines is unclear.…”
Section: Impacts Of Wind Turbine Proximity On Property Values In Massmentioning
confidence: 99%